PEMIKIRAN POLITIK ISLAM MUSTOFA BISRI DALAM PUISI: PERSFEKTIF HERMENEUTIKA KEROHANIAN - Erfi Firmansyah (Faculty of Humanities, Jember University, 2012)
The study generally aims to determine how the Islamic political thought in poetry KH Mustafa Bisri , and find use hermenutik spiritual approach in reviewing poetry. Mustafa Bisri poems is , in principle, can be approximated by hermenutik approach to spirituality. Poetry KH Mustafa Bisri not too difficult to understand. Based on a study conducted on the ten poems KH Mustafa Bisri , it can be seen that Islam is very strong political element in his poems. So , in an effort to gain and retain political power displayed in his poems Always he was guided by the teachings of Islam which has always been inherent in him. The views and criticisms Mustafa Bisri through his poems based on the moral Always political Islam that promotes good moral or good morals. Through poetry poet reminded various parties in Indonesia to improve themselves and redirecting itself on the completion of the reform as an act of gratitude towards independence had been achieved by the Indonesian nation. Keywords : Hermeneutics Spirituality , Poetry Islamic , Islamic Politics